2008
DOI: 10.1038/bjp.2008.113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chondroitin sulphate in a rabbit model of atherosclerosis aggravated by chronic arthritis

Abstract: Background and purpose: Among the agents employed to manage osteoarthritis, chondroitin sulphate (CS) is a natural glycosaminoglycan with an anti-inflammatory effect on joint cells. CS might also influence the inflammatory component of atherosclerosis. Our aim was to examine the effect of CS administration on vascular injury and on markers of systemic inflammation in a rabbit model of atherosclerosis aggravated by systemic inflammation provoked by chronic antigen-induced arthritis. Experimental approach: Ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 46 publications
0
31
1
4
Order By: Relevance
“…We recently showed that administering chondroitin sulfate (CS) to rabbits with AIA-AT reduced the concentration of inflammatory markers in serum and produced a clear improvement in the inflammatory content of femoral atherosclerotic lesions, as well as a decrease in the aortic lesions (14). GS and CS are saccharides with a different chemical composition, and, while GS is an amino monosaccharide, CS is a glycosaminoglycan formed by the polymerization of the glucuronic acid and galactosamine dissacharides with different sulfation sites.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that administering chondroitin sulfate (CS) to rabbits with AIA-AT reduced the concentration of inflammatory markers in serum and produced a clear improvement in the inflammatory content of femoral atherosclerotic lesions, as well as a decrease in the aortic lesions (14). GS and CS are saccharides with a different chemical composition, and, while GS is an amino monosaccharide, CS is a glycosaminoglycan formed by the polymerization of the glucuronic acid and galactosamine dissacharides with different sulfation sites.…”
Section: Resultsmentioning
confidence: 99%
“…In another recent study (Herrero-Beaumont et al 2008), CS administration reduced the concentration of the proinflammatory molecules, C-reactive protein (CRP) and IL-6, and the nuclear translocation of NF-jB in a rabbit model of atherosclerosis aggravated by chronic arthritis (Herrero-Beaumont et al 2008). Moreover, CS decreased the percentage of rabbits with atherosclerosis and chronic arthritis, which developed vascular lesions in the aorta.…”
Section: Cs Anti-inflammatory Activity In Animal Modelsmentioning
confidence: 99%
“…However, to date, no biological activity has ever been tested and confirmed for these nonextractive polysaccharides. In this study, we report the effect of two different nonanimal CSs produced using a patented biotechnological process in adjuvant arthritis (AAR), an animal model of polyarthritis (OA and rheumatoid arthritis) widely used for preclinical tests [15,16] and previously adopted to evaluate the activity of a pharmaceutical-grade CS of extractive origin [17]. …”
Section: Introductionmentioning
confidence: 99%